2018
DOI: 10.1111/jon.12558
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors That Affect the Relationship between Head Circumference and Brain Volume in Very‐Low‐Birth‐Weight Infants

Abstract: Although HC has predictive value for TBV in VLBW infants, care should be taken in infants with low BBW (BBW less than 600 g) or dolichocephaly (MRI-based cranial index less than .68), which were related to overestimation of TBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In preterm infants however, head circumference often poorly reflects brain size due to head deformities and increased extracerebral fluid. 3,4 Brain imaging techniques can add valuable information on the actual size of the brain. MR imaging is considered the most reliable method but is not bedside-available and is expensive, limiting the possibility of serial repeat imaging.…”
mentioning
confidence: 99%
“…In preterm infants however, head circumference often poorly reflects brain size due to head deformities and increased extracerebral fluid. 3,4 Brain imaging techniques can add valuable information on the actual size of the brain. MR imaging is considered the most reliable method but is not bedside-available and is expensive, limiting the possibility of serial repeat imaging.…”
mentioning
confidence: 99%
“…Children with a head circumference more than two standard deviations (SDs) above or below the norm are recommended for further neurological evaluation and necessary treatment. New advances in radiology have provided methods to estimate brain volume with greater sensitivity and precision than what previous methods could achieve [5,6] . Studies have found that magnetic resonance imaging (MRI)-based brain volume calculation may be the better imaging-based technique to describe the development of the brain in both neonates and children [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…New advances in radiology have provided methods to estimate brain volume with greater sensitivity and precision than what previous methods could achieve. [ 5 , 6 ] Studies have found that magnetic resonance imaging (MRI)-based brain volume calculation may be the better imaging-based technique to describe the development of the brain in both neonates and children. [ 5 , 6 ] It can also provide real-time analyses of brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Cephalometry is carried out utilizing several methods, including photogrammetry, ultrasound, CT scan, MRI, and the use of standard lateral skull radiographs or cephalograms. 6,7 Determination of anthropometric measurements and reference ranges of each ethnic group is therefore essential for indicating the degree of deviations from normal. Moreover, background newborn anthropometric data, which could assess deviations from normal, are generally lacking in developing countries.…”
Section: Introductionmentioning
confidence: 99%